Elucidating the role of precipitated phase particles in modifying creep properties of as-cast Mg-Bi/Sn-based alloys - Gang Xu; Wei-li Cheng; Yi-hao Luo; Hui Yu; Li-fei Wang; Hang Li; Hong-xia Wang; Jin-hui Wang (Journal of Magnesium and Alloys)
The study developed the three alloy systems with different precipitates and examined the role of precipitated phase particles in modifying the creep properties of as-cast Mg-10Bi-0.5Mn-0.5Ag (BMQ1000), Mg-5Bi-5Sn-0.5Mn-0.5Ag (BTMQ5500) and Mg-10Sn-0.5Mn-0.5Ag (TMQ1000) alloys at temperatures ranging from 423 to 473 K and stresses of 45–85 MPa. The values of n for the BMQ1000, BTMQ5500, and TMQ1000 alloys were determined as 6.67, 5.75, and 5.92, respectively. Moreover, the activation energy for these alloys was found to be 164.71, 134.68, and 135.93 kJ/mol, respectively. The results suggested that the creep properties followed the order of BTMQ5500 > TMQ1000 > BMQ1000. A coarse and uneven distribution of the Mg3Bi2 precipitated phase in the BMQ1000 alloy leads to a feeble pining effect on dislocation slipping and generates substantial stress concentrations. For TMQ1000 alloy, while the nanoscale Mg2Sn precipitates have a stronger barrier effect on dislocations than the Mg3Bi2 in the BMQ1000 alloy, their ability to inhibit dislocation climbing is comparatively weak. Furthermore, it was found that Mg2Sn precipitates and α-Mg exhibited a preferential orientation relationship of (020)Mg2Sn // (–1010)Mg, and the morphology of the precipitated phase transformed in a way that hinders dislocation movement effectively. In addition, elastic interactions between the precipitated phases are identified. The above-mentioned factors are largely responsible for the notable enhancement in creep resistance. Further, it is ascertained that cross-slip and pyramidal 〈c + a〉 slip are primary creep mechanisms in the BMQ1000 alloy. In contrast, the dominant mechanisms in TMQ1000 and BTMQ5500 alloys are dislocation climb and pyramidal 〈c + a〉 slip. Moreover, stacking faults (SFs) and twinning assist in the creep deformation of the BTMQ5500 alloy.